2012
DOI: 10.1145/2366145.2366199
|View full text |Cite
|
Sign up to set email alerts
|

Structure recovery by part assembly

Abstract: Figure 1: Given single-view scans by the Kinect system, containing highly noisy and incomplete 3D scans (upper left) and corresponding RGB images (lower left), our approach is able to faithfully recover their underlying structures (yellow) by assembling suitable parts (red) in the repository models (blue). AbstractThis paper presents a technique that allows quick conversion of acquired low-quality data from consumer-level scanning devices to high-quality 3D models with labeled semantic parts and meanwhile thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
138
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 54 publications
0
138
0
Order By: Relevance
“…Our work also shares resemblance to the large body of methods on structure-based shape analysis and modeling [17], [18], [19], [20], [21], [22], [23], wherein high-level shape structures are identified with low-dimensional parts of different sizes, positions, and interactions. Gal et al [17] demonstrated that working with a set of 1D feature curves extracted from engineered objects, and preserving their intra-and inter-relations while deforming the shapes lead to an intuitive manipulation framework.…”
Section: Related Workmentioning
confidence: 66%
See 2 more Smart Citations
“…Our work also shares resemblance to the large body of methods on structure-based shape analysis and modeling [17], [18], [19], [20], [21], [22], [23], wherein high-level shape structures are identified with low-dimensional parts of different sizes, positions, and interactions. Gal et al [17] demonstrated that working with a set of 1D feature curves extracted from engineered objects, and preserving their intra-and inter-relations while deforming the shapes lead to an intuitive manipulation framework.…”
Section: Related Workmentioning
confidence: 66%
“…Gal et al [17] demonstrated that working with a set of 1D feature curves extracted from engineered objects, and preserving their intra-and inter-relations while deforming the shapes lead to an intuitive manipulation framework. Shen et al [19] recovered structures by combining existing labeled parts from different objects, considering both partial matching with the acquired data and the interactions between parts. Laga et al [21] exploited the context of structural relationships between shape parts and use them, in conjunction to their geometry, as cues for functionality recognition.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For an extensive discussion of history and development of ergonomics in the context of chairs we recommend Cranz's book [17], especially Chapters 3 and 5. As examples of linking geometric form with function, Shen et al [18] utilize object structure for effective object assembly, while the AttribIt [19] system links semantic tags to object parts and their coupled variations.…”
Section: Related Workmentioning
confidence: 99%
“…[28] uses 3D CAD models as templates for a sliding window search. Shen et al [25] use a database of segmented models and assembly-based modeling algorithms to reconstruct novel 3D models. Nan et al [20] integrate a region growing segmentation algorithm with object recognition for cluttered indoor scene understanding.…”
Section: Related Workmentioning
confidence: 99%